2019
DOI: 10.1186/s42787-019-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluids flow over a permeable unsteady stretching surface with non-uniform heat source/sink in the presence of inclined magnetic field

Abstract: This work analyzes the unsteady two-dimensional nanofluid flow over a vertical stretching permeable surface in the presence of an inclined magnetic field and nonuniform heat source/sink. Four different types of nanoparticles, namely silver Ag, copper Cu, alumina Al 2 O 3 , and titania TiO 2 , are considered by using water as a base fluid with the Prandtl number Pr = 6.785. The governing partial differential equations are transformed to coupled non-linear ordinary differential equations by appropriate similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 42 publications
(62 reference statements)
0
40
0
Order By: Relevance
“…They implemented the Chebeshev collocation method to attain the desired results. Elgazery 23 presented the magnetic field impact on nanofluid flow over an unsteady permeable stretching surface by considering a nonuniform heat source/sink. Ibrahim and Tulu 24 researched the MHD flow of a nanofluid with heat transfer treatment embedded in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…They implemented the Chebeshev collocation method to attain the desired results. Elgazery 23 presented the magnetic field impact on nanofluid flow over an unsteady permeable stretching surface by considering a nonuniform heat source/sink. Ibrahim and Tulu 24 researched the MHD flow of a nanofluid with heat transfer treatment embedded in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…A series of numerical calculations has been accomplished by employing a useful numerical technique called the Keller-box method on system of Equations (12)- (15) with their appropriate boundary settings (15) to achieve insight into the physical situation of flow configuration. These computations are attained for various values of Brownian motion factor Nb, thermophoresis assumed by Nt, magnetic factor M, buoyancy factor λ, solutal buoyancy constraint δ, inclination factor ζ, Prandtl number Pr, Lewis number Le, radiation effect N, Brinkman parameter β 1 , suction or injection parameter S, and material factor K, which are presented in different tables and figures.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Rafique et al [11] investigated the flow of Casson nanofluid towards an inclined surface. For details, see references [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the rate of heat transfer declined as there was increase in the heat generation/absorption values. Similarly, in several other studies, the characteristic of heat transfer was analyzed due to the fluid flow over stretching sheet [18][19][20]. Ganga et al [21] explored viscous and Ohmic dissipation effects on MHD flow subjected to an upright plate in addition to heat generation/absorption effect on nanofluid.…”
Section: Introductionmentioning
confidence: 99%